2018
DOI: 10.1111/rda.13315
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial transcript profile of progesterone‐regulated genes during early pregnancy of Water Buffalo (Bubalus bubalis)

Abstract: Progesterone (P ) plays a key role in the establishment and maintenance of pregnancy in most mammals. Unravelling the expression of progesterone-regulated genes can expand the understanding of the embryonic mortality. Accordingly, we studied the relative mRNA expression of the P -regulated genes in the buffalo. Uteri were collected from the abattoir and categorized into nonpregnant late luteal phase, stage I (28-38th days of gestation) and stage II (48-56th days of gestation) of pregnancy (n = 6/group). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The FBP1 gene plays an important role in the glucosynthesis [ 31 ], while the FBP2 gene was shown to be related to milk productions traits [ 32 ], activating various metabolic processes in time of increased demands of high milk production [ 33 ]. The gene CTSL (cathepsin L) seems to be interesting from multiple angles, as it had been shown to influence carcass traits, production of milk [ 34 ] and reproductive traits [ 35 ]. The ISCA1 was found to be associated with multiple mitochondrial dysfunctions [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The FBP1 gene plays an important role in the glucosynthesis [ 31 ], while the FBP2 gene was shown to be related to milk productions traits [ 32 ], activating various metabolic processes in time of increased demands of high milk production [ 33 ]. The gene CTSL (cathepsin L) seems to be interesting from multiple angles, as it had been shown to influence carcass traits, production of milk [ 34 ] and reproductive traits [ 35 ]. The ISCA1 was found to be associated with multiple mitochondrial dysfunctions [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced expression of the LGALS3BP gene in PBMCs indicated its role in the adhesion of the conceptus to the endometrium (Bauersachs et al ., 2006). The expression of LGALS3BP was upregulated in early (day 20) pregnant buffaloes compared to the same animals at day 0 d and to the non-pregnant group at day 20, indicating its potential role in establishing a pregnancy (Baba et al ., 2019). Our results agree with the high expression of LGALS3BP observed in pregnant heifers (Rocha et al ., 2020), who showed that PBMC expression of LGALS3BP and other INFT-stimulated genes ( IFI6, IFI44, RSAD2, OAS2, IFITM2 and CLEC3B ) was affected by pregnancy status at day 18 post insemination.…”
Section: Discussionmentioning
confidence: 99%
“…Its increased expression in this cell type is interesting because the involvement of LGALS3BP in the adhesion process of the conceptus is limited to the luminal epithelium of the uterus (Bauersachs et al, 2006), and, in addition to the different function of cervical and endometrial cells, they are not exposed to the same stimuli during pregnancy (Kunii et al, 2018). However, Baba et al (2019) also observed that LGALS3BP modulates the maternal immune response during early pregnancy in buffaloes, suggesting that its higher expression at this period has an important role in maternal recognition of pregnancy and implantation.…”
Section: Short Communication Physiologymentioning
confidence: 99%